2005
DOI: 10.1080/13880200500220771
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activities of the Leaf Oils of EightCinnamomum. species AgainstAedes aegypti. andAedes albopictus.

Abstract: The leaf oils of eight Cinnamomum species (C. rhyncophyllum Miq., C. microphyllum Ridl., C. pubescens Kochummen, C. mollissimum Hook. f., C. impressicostatum Kosterm, C. scortechinii Gamb., C. sintoc Bl., and C. cordatum Kosterm) were investigated for their larvicidal and adulticidal activities against Aedes aegypti (Aedes aegypti Lynn) and Aedes albopictus (Aedes albopictus Skuse). Acute mortalities of the fourth instar larvae and the adult mosquitoes were determined according to the standard WHO methods. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 9 publications
3
40
0
1
Order By: Relevance
“…The search for new strategies with natural products to control destructive insects and vectors of diseases is desirable due to the prevalence of vector resistance to synthetic insecticides, problem of toxicity, non-biodegradable effects, and effects on non-target organisms (Jantan et al 2005). Extracts from plants may be alternative sources of mosquito control agents since they constitute rich sources of bioactive compounds that are biodegradable into non-toxic products and potentially stable (Amer and Melhorn 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The search for new strategies with natural products to control destructive insects and vectors of diseases is desirable due to the prevalence of vector resistance to synthetic insecticides, problem of toxicity, non-biodegradable effects, and effects on non-target organisms (Jantan et al 2005). Extracts from plants may be alternative sources of mosquito control agents since they constitute rich sources of bioactive compounds that are biodegradable into non-toxic products and potentially stable (Amer and Melhorn 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, one of the major constituent, safrole was found to possess larvicidal activity against two mosquitoes, A. aegypti and A. albopictus [21,22]. However, myristicin was shown to have contact and fumigant toxicity against several insect/mites and to exhibit strong synergistic activity because it has been demonstrated to possess strong inhibitory effects on many P450s, such as houseflies (Musca domestica) [23], hairy caterpillars (Spilarctia obliqua) [24], armyworms (Pseudaletia unipuncta) [25], navel orangeworm (Amyelois transitella) [26], and house dust mites (Dermatophagoides farinae, D. pteronyssinus) and mould mites (Tyrophagus putrescentiae) [27].…”
Section: Discussionmentioning
confidence: 99%
“…The search for new strategies or natural products to control vectors of diseases is desirable due to the prevalent occurrence of vector resistance to synthetic insecticides and the problem of toxic nonbiodegradable residues contaminating the environment and undesirable effects on nontarget organisms (Jantan et al, 2005). Essential oils from plants may be an alternative source of mosquito larval control agents, since they constitute a rich source of bioactive compounds that are biodegradable and potentially suitable for use in integrated management programs.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils from plants may be an alternative source of mosquito larval control agents, since they constitute a rich source of bioactive compounds that are biodegradable and potentially suitable for use in integrated management programs. Much effort has, therefore, been focused on the effectiveness of plant essential oils against mosquito larvae because of their broad spectrum of activity against insects, low mammalian toxicity, and ability to degrade rapidly in the environment (Jantan et al, 2005;Morais et al, 2007;Cheng et al, 2008;Silva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%